Impact of contextual determinants towards the disposition bias of individual investors in the Sri Lankan stock market - Buddhika, H.J.R.; Ediriwickrama, T.C. (International Journal of Accounting & Business Finance, 2022)
The findings are important for individual stock investors and potential investors significantly; can be attentive to their peculiar cognitive and emotive factors in their accurate investment decisions. Among the 306 individual investors in the Colombo Stock Exchange (CSE) was used as survey model. Through standardized questionnaires from earlier research studies, the events, beliefs, behavioral consequences, loss aversion, disposition, and investor sentiment assessed. AMOS software was used for the structural equation modelling (SEM) analysis of the data. The empirical data supported that loss aversion and investor sentiment positively impacted the disposition bias of individual investors. The events, beliefs and behavioral consequences (emotions) do not considerably drive factors of disposition bias in the Sri Lankan stock market. The results showed that loss aversion and sentiment are the primary causes of disposition bias, which is supported by the previous scholar's findings. The study supported loss aversion through disposition bias and the mediational impact of events. The main theoretical contribution is; the ABC model does not fully support in the Sri Lanka context to address the disposition where the loss aversion contributes to the execution of the disposition and moderating by investor sentiment. The existing outcomes will be useful for the investors, prospective investors and the stockbroker firms for maintaining and leading to substantial assertive decision making reducing of having biased decisions. The study identified the biases of a person's personality about nature in the early structure before leading to disposition bias. The second half of 2020 was used for which statistics were collected, and only the Sri Lankan market was included in the generalization. The macroeconomic implications and the institutional investors do not consider for the study due to complexity. The association between loss aversion and disposition bias was proved via the investigation. The paper recommended that investors with risk-averse prime for the disposition and the disposition is heavily influenced by a person's loss-averse personality, which is controlled by investor sentiment.
Keywords: Disposition Bias; Loss Aversion; Colombo Stock Exchange; Individual Investors